Parental Guidance, Learning Media, and Classroom Climate in Shaping the Learning Process and Motivation of Madrasah Ibtidaiyah Students - Darmawan, Didit (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2026)
This literature study aims to analyze the role of parental guidance, learning media, and classroom climate in shaping the learning process and motivation of students in Islamic elementary schools (Madrasah Ibtidaiyah). The method used is qualitative library research with a thematic synthesis approach following systematic literature review procedures. The results indicate that quality parental guidance, characterized by emotional warmth, consistent mentoring, daily role modeling, and open communication, builds the foundation for intrinsic motivation and robust learning habits from home. Appropriate and varied learning media, selected according to material characteristics and student development levels, bridge abstract concepts with concrete experiences, make learning more engaging, and accommodate diverse learning styles. A positive classroom climate, created through respectful teacher interaction, supportive peer relationships, and clear structures and routines, provides a psychologically safe environment for students to explore, ask questions, and develop their potential. These three factors complement each other and collectively form an educational ecosystem that enables students not only to achieve academic success but also to develop a lifelong love for learning. This study contributes theoretically to enriching the ecological perspective on elementary education and practically provides reflective foundations for parents, teachers, and madrasah principals in optimizing their respective roles.